Comparison between Surgical and Conservative Treatments in Isolated Lateral Compartment Syndrome of the Lower Leg: A Case Report - Gwak, Heui-Chul; Seo, Young-Chae; Jung, Soo-Hwan; Kim, Dae-Yoo (Journal of Korean Foot and Ankle Society, 2022)
Lateral compartment syndrome of the lower leg is rarely observed. Hence, there may be difficulty in diagnosis as its clinical patterns are different and more complicated than usual. We report two rare cases of a 20-year-old and a 28-year-old diagnosed with isolated lateral compartment syndrome who had either a surgical or conservative treatment. The comparison was done by analyzing the progression of neurological manifestation, electromyography, and nerve conduction study for two years. In the final follow-up, the patient who underwent the surgical treatment showed a shorter recovery time. However, both patients showed a full recovery from neurologic deficits. KCI Citation Count: 0